The Diptera of Panama. II. A first benchmark for the family Chironomidae - Armitage, Brian J.; Andersen, Trond; Giłka, Wojciech; Sánchez, Kayla N. Castillo; González, Tomás A. Ríos; E., Yusseff P. Aguirre (Zootaxa, 2025)
The Chironomidae (Insecta: Diptera) are among a number of aquatic invertebrate groups which have received scant attention in Panama. This paper brings together information from the published literature, personal comments by colleagues, and current research to produce a first benchmark of knowledge about this dipteran family. To date, we have discovered 57 named species in 31 genera distributed among five chironomid subfamilies. In addition, 22 unassociated genera/subgenera (without identified species) are listed. The majority of the taxa recorded belong to the subfamily Chironominae (40 named species in 17 genera, plus 11 unassociated genera/subgenera). Of the 79 total number of species and unassociated taxa of the genus or subgenus rank presented in this paper, 43 are new country records for Panama.